Quasi-LPV PI control of TRMS subject to actuator saturation - Goyal, Jitendra Kumar; Aggarwal, Shubham; Ghosh, Sandip; Kamal, Shyam; Dworak, Pawel (IET control theory & applications, 2020)
This study is concerned on the design of a quasi-linear parameter varying (qLPV) proportional–integral (PI) controller for twin rotor multiple-input multiple-output systems (TRMS). The non-linear model is represented as a qLPV polytopic plant with an affine dependence on a non-linear parametric function of the pitch angle. This representation retains the exact model as opposed to the conventional linearisation around an operating point. Due to the availability of the pitch angle measurement, the non-linear parameter can be obtained in real-time and the controller is designed using qLPV technique. To deal with limited control input for such systems, the proposed controller design also considers the actuator saturation that yields controller with practical gains without any additional gain bound criterion. Further, the transient tracking performance is also considered in the design by using closed-loop eigenvalues assignment in desired damping regions. The control synthesis problem is formulated in the form of linear matrix inequalities for $\mathcal {L}_2$L2 gain based performance criterion. The designed controller is validated on a two-degree of freedom helicopter experimental setup. Finally, to demonstrate the effectiveness of the proposed design, a comparative analysis is done with the existing algorithms. Also, the efficacy of the decentralised controller vis-a-vis the centralised one is presented.